The Importance of Constitutional Interpretation in Establishing the Foundations of Fundamental Rights and Freedoms - سليم, شلال عواد (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
This research addresses the significance of constitutional interpretation in enhancing fundamental rights and freedoms by examining methodologies for interpreting constitutional texts, such as the restrictive method that limits flexibility, the historical-social approach that seeks to understand historical contexts, and the evolving interpretation method that allows for the adaptation of rights to social transformations. In the second section, the focus is on the technical means of interpretation, divided into internal means, including preparatory works and historical sources, and external means represented by international declarations and democratic standards. The research highlights how each of these methodologies and means contributes to a comprehensive understanding of individual rights and ensures their protection within contemporary legal contexts.